2018
DOI: 10.1017/s0144686x18001356
|View full text |Cite
|
Sign up to set email alerts
|

Middle-aged women negotiating the ageing process through participation in outdoor adventure activities

Abstract: This study sought to examine the motivations middle-aged women give for belonging to an outdoor adventure group. As part of this, how the women were negotiating the ageing process was also examined. Fourteen women aged 36–64 (average age 51.4 years) were individually interviewed with the purpose of exploring their perceptions, values, motivations and the beliefs they attach to their participation. Findings highlight the women's belief that participation delays the ageing process, gives them confidence in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Women have historically been under-represented in outdoor tourism research and practice, though there is now a growing recognition of gender differences ( Evenson et al, 2002 ; Pohl, Borrie, & Patterson, 2000 ), across the entire life course ( Carmichael, Duberley, & Szmigin, 2015 ; Cosgriff, Little, & Wilson, 2009 ; Wharton, 2018 ). Women may have different motivations and learning styles than men ( Kiewa, 1994 ; Whittington, 2006 ); face different barriers and encouragements to take part in various outdoor activities ( Doran, Schofield, & Low, 2018 ; Little, 2002 ; Loeffler, 1997 ; McNiel, Harris, & Fondren, 2012 ; Morris, Van Riper, Kyle, Wallen, & Absher, 2018 ); and attach importance to different aspects and achievements ( Kiewa, 2001 ; Nolan & Priest, 1993 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Women have historically been under-represented in outdoor tourism research and practice, though there is now a growing recognition of gender differences ( Evenson et al, 2002 ; Pohl, Borrie, & Patterson, 2000 ), across the entire life course ( Carmichael, Duberley, & Szmigin, 2015 ; Cosgriff, Little, & Wilson, 2009 ; Wharton, 2018 ). Women may have different motivations and learning styles than men ( Kiewa, 1994 ; Whittington, 2006 ); face different barriers and encouragements to take part in various outdoor activities ( Doran, Schofield, & Low, 2018 ; Little, 2002 ; Loeffler, 1997 ; McNiel, Harris, & Fondren, 2012 ; Morris, Van Riper, Kyle, Wallen, & Absher, 2018 ); and attach importance to different aspects and achievements ( Kiewa, 2001 ; Nolan & Priest, 1993 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…From a health perspective, these aspects reflect the diagnosis, design, dose, and duration of nature tourism psychotherapies (Buckley, Brough, and Westaway 2018; Shanahan et al 2016). Different activities (Pasanen et al 2019; Svensson et al 2019, 2021), for different durations (Bélanger et al 2019; Chen, Zou, and Gao 2020; Labudek et al 2021; Legrand and Mille 2009; Sanz-Remacha et al 2021; White et al 2019), in different environments (Biedenweg, Scott, and Scott 2017; Bielinis et al 2019; Jarvis et al 2020; White et al 2021; Wyles et al 2019), and countries (Buckley and Brough 2021; Tester-Jones et al 2020; White et al 2021) can improve mental health and wellbeing for people of different genders (Buckley and Westaway 2020, 2021; Doran, Schofield, and Low 2018); ages (Cleary et al 2020; Engemann et al 2020; Hartley et al 2021; Jackson et al 2021; Keith et al 2021; Putra et al 2021; Wharton 2020); interests and motivations (Roberts, Jones, and Brooks 2018); mental states or illnesses (Besser 2021; Tester-Jones et al 2020); and personalities (Wang et al 2017; White et al 2016), especially nature connectedness (Martin et al 2020; Richardson and McEwan 2018; Rickard and White 2021).…”
Section: Mental Health Research In Different Tourism Subsectorsmentioning
confidence: 99%
“…Acceptance as Olympic sports, and large-scale corporate endorsement, of adventure activities such as surfing, climbing and kayaking, has repositioned their practitioners as athletes rather than dropouts. Qualitative research on adventure participants has shown that they exercise socially admired personality traits such as careful judgment and advance preparation, and that adventure experiences generate positive psychological outcomes, some transformative (Hickman et al 2018; Holmbom, Brymer, and Schweitzer 2017; Wharton 2020).…”
Section: Mental Health Research In Different Tourism Subsectorsmentioning
confidence: 99%
“…Research on nature-based outdoor therapies includes differences between: genders (Buckley & Westaway, 2020Doran, Schofield, & Low, 2018;Kiewa, 1994); ages (Fenton et al, 2018;Wharton, 2018); interests and motivations (Roberts, Jones, & Brooks, 2018); mental states (Tester-Jones et al, 2020); activities (Pasanen et al, 2019;Svensson et al, 2019); durations (Bélanger et al, 2019;Legrand & Mille, 2009;White et al, 2019); and settings and ecosystems (Bielinis et al, 2019;Wyles et al, 2017), including biodiversity (Lindemann-Matthies & Matthies, 2018; Methorst et al, 2021). A similar range of research factors will be required for adventure-based outdoor therapies (Buckley, 2018b(Buckley, ,c, 2020a.…”
Section: Is Adventure Tourism Therapeutic?mentioning
confidence: 99%